Hejka!
1)
f(x) = 2(x - 4)² - 7
f(x) = 2(x² - 8x + 16) + 7
f(x) = 2x² - 16x + 32 + 7
f(x) = 2x² - 16x + 39
2)
f(x) = -3(x + 2)² + 6
f(x) = -3(x² + 4x + 4) + 6
f(x) = -3x² - 12x - 12 + 6
f(x) = -3x² - 12x - 6
3)
f(x) = -(x + 2)(x - 5)
f(x) = -(x² - 5x + 2x - 10)
f(x) = -(x² - 3x - 10)
f(x) = -x² + 3x + 10
4)
f(x) = 4(x + 3)(x - 4)
f(x) = 4(x² - 4x + 3x - 12)
f(x) = 4(x² - x - 12)
f(x) = 4x² - 4x - 48
5)
f(x) = ½(x - 6)(x - 1)
f(x) = ½(x² - x - 6x + 6)
f(x) = ½(x² - 7x + 6)
f(x) = ½x² - 3,5x + 3
Pozdrawiam! - Julka